BOOK REVIEW PENGANTAR HUKUM DAGANG (INTRODUCTION TO COMMERCIAL LAW) - Wulandari, Catur (UI Scholars Hub, 2014)
According to Apeldoorn to give a definition of the “law” is a difficult thing, but nevertheless provides a definition would be very valuable for those who just starting to learn something. One example is the definition of Commercial Code which is contained in the book by Purwosucipto. In his book, Purwosucipto said that the Commercial Law is a special law arising out from the Legal Engagement in the company activities. This severely limits the definition of Commercial Law only on the engagements aspects arising only from the activities of the company. But according to the Authors of this book, explanation about Commercial Law proposed by Purwosucipto needs to be expanded, not just limited to the Legal Engagement, but also covers all legal instrument written or unwritten, that governs all activities in the field of the trade.